2017
DOI: 10.31018/jans.v9i2.1306
|View full text |Cite
|
Sign up to set email alerts
|

Mulching: A viable option to increase productivity of field and fruit crops

Abstract: Mulching plays an important role in production of agricultural and horticultural crops in the current scenario of declining water table, soil degradation and climate change. The main objectives of mulching are to prevent loss of water by evaporation, prevention of soil erosion, weed control, to reduce fertilizer leaching, to promote soil productivity, to enhance yield and quality of field and fruit crops. So, mulching is useful to save our underground water resource, soil and environment for sustainable crop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Thus, depicted the suitability of black polythene mulch over the other treatments. The results on chemical studies for NPK value of the treated soil samples lies in close conformity with the earlier reports of Chaudhary and Iqbal [10], Mirazalva et al [11], Gao et al [17] and Kaur & Bons [18].…”
Section: Nutrient Content: Nitrogen Phosphorous and Potassium (Npk)supporting
confidence: 92%
“…Thus, depicted the suitability of black polythene mulch over the other treatments. The results on chemical studies for NPK value of the treated soil samples lies in close conformity with the earlier reports of Chaudhary and Iqbal [10], Mirazalva et al [11], Gao et al [17] and Kaur & Bons [18].…”
Section: Nutrient Content: Nitrogen Phosphorous and Potassium (Npk)supporting
confidence: 92%
“…Overall, the present study observed, until three years after plastic film cover application, significant differences in the vegetative growth of sweet orange trees. Such results are justified, since, according to Kaur;Bons (2017), Farias-Larios et al (1996, Rajapakse;Kelly (1994) and Tindall et al (1991), in order to accelerate its development, plants require solar radiation as an energy source to perform photosynthesis, higher soil temperature, increased availability and absorption of water and nutrients by roots and increased number and activity of soil microorganisms, which are all factors associated with the use of soil cover with plastic films.…”
Section: Resultsmentioning
confidence: 99%
“…Soil TOC is a key index through which to measure soil quality [ 16 ]. The results showed that fertilization could significantly increase the TOC of soil, and the effect of the exogenous organic carbon, such as straw and organic fertilizer, was more significant than that of the NPK treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, burying straw in soil improves the water storage of the topsoil [ 15 ]. Furthermore, burying straw in soil improves the soil structure and biological activities, as well as reduces soil degradation, regulates heat, and ultimately increases the productivity and sustainability of cropping systems [ 16 ]. However, there is very limited information on the effects of the partial replacement of chemical fertilizer with organic fertilizer, as well as on straw returning on enzyme activity and organic carbon contents in the black soil located in the northern Anhui region of China.…”
Section: Introductionmentioning
confidence: 99%